The Role of Green Marketing and Sustainability Practices in Increasing Brand Equity in the Indonesian E-commerce Sector - Zulkifli Noor, Zulki (Dinasti Publisher, 2025)
This study aims to analyze the effect of green marketing and sustainability practices on brand equity in the Indonesian e-commerce sector. A quantitative approach with an explanatory research design was used to test the relationship between variables. Data were collected through an online survey using a structured questionnaire from 200 respondents who are e-commerce consumers in Indonesia. The analysis was conducted using Structural Equation Modeling (SEM) to test the direct and indirect effects. The results showed that green marketing has a significant positive effect on brand equity (? = 0.42, p < 0.001). Sustainability practices also have a positive effect on brand equity (? = 0.38, p < 0.004). In addition, sustainability practices are proven to mediate the relationship between green marketing and brand equity with an indirect effect of 0.15 (p = 0.032). These findings indicate that green marketing strategies integrated with sustainability practices can increase consumer loyalty and trust, which ultimately strengthen brand equity. This study provides theoretical contributions to the green marketing and sustainability literature, and offers practical guidance for e-commerce companies to adopt environmentally friendly strategies effectively. Managerial implications include the importance of transparent communication and consistent adoption of sustainability practices to create competitive advantage. This study also opens up opportunities for further exploration in other sectors or with different methods.